A dynamic optimization method for power distribution network operation with high ratio photovoltaics. Issue 21 (16th September 2022) - Liu, Keyan; Zhan, Huiyu; Wei, Yuhan; Kang, Tianyuan
Abstract: With the high ratio distributed photovoltaics (PVs) penetration to the distribution network (DN), the bearing capacity, integration capacity, consuming capacity and controlling capacity of DN for PVs are all facing great challenges. Enhancing the flexible regulation and operation optimization capabilities of DN have become key factors to satisfy these new challenges. For the operation optimization problem of high ratio PVs penetration, a novel quasi‐equal curtailment ratio (QCR) constraint of PVs is proposed in the dynamic optimization method for DN operation. Firstly, the uncertainty of high ratio PVs and their active power deviations are discussed. And a dynamic optimization framework of PVs based on optimal power flow (OPF) has been proposed. Secondly, the optimization model for high ratio PVs is formulated with multi‐objective of maximum PVs output, minimum voltage deviation and minimum line loss, under the equality and inequality constraints of power flow, PVs power generation limit, QCR of PVs and so on. Then the multi‐objective optimization problem (MOP) is transformed into a single‐objective optimization problem (SOP) by weighting coefficients, and solved by sequential quadratic programming (SQP) with trust‐region (TR) searching algorithm. Finally, the proposed method is tested, verified and compared with the primal dual interior point (PDIP) and traditional SQP algorithms in IEEE 33‐bus, PG&E 69‐bus, 292‐bus and 1180‐bus test cases. The experimental results show the rapidity and robustness of the proposed method.